Customer Relationship Management System Study : Software System, Architecture And Transaction Analysis - Chandy, Elcy Thomas (2002)
The purpose of this research project has been to conduct a study on Customer Relationship Management (CRM) System. Enabling technologies for CRM includes a front-end Application System for the automation of Customer Relationship Management, an Enterprise Application Interface (EIA) to integrate the databases and CRM databases.